The Role of the Teaching Assistance Program in Developing Students' Initiative, Discipline, and Speaking Skills - Zahri Basri Yani; Nadia Sri Yemim Munthe; Marthauli Hotlian Pasaribu; Etik Triwahyuni; Testy Ariance Loren (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the role of the Teaching Assistance Program in developing students’ discipline, initiative, and speaking skills at SMP Negeri 50 Batam. The study employed a descriptive qualitative approach supported by quantitative data through a case study design conducted over one academic semester. The research subjects consisted of eighth- and ninth-grade students who actively participated in the Teaching Assistance Program, along with the mentors who guided them. Quantitative data were collected using rubric-based assessment instruments, including a Likert scale for discipline and initiative skills and a performance-based rubric for speaking skills, administered at the beginning and end of the program. Qualitative data were obtained through participatory observations, in-depth interviews with students and mentors, and document analysis of program planning and weekly reports. The findings indicate that the Teaching Assistance Program significantly contributes to improving students’ discipline, initiative, and speaking skills. The integration of qualitative and quantitative data provides a comprehensive picture of the program’s effectiveness and highlights the relevance of the Teaching Assistance Program as a strategy for developing students’ character and competencies at the junior secondary school level.